2004
DOI: 10.1136/bmj.38246.594873.7c
|View full text |Cite
|
Sign up to set email alerts
|

The Lambeth Early Onset (LEO) Team: randomised controlled trial of the effectiveness of specialised care for early psychosis

Abstract: Objective To evaluate the effectiveness of a service for early psychosis. Design Randomised controlled clinical trial. Setting Community mental health teams in one London borough. Participants 144 people aged 16-40 years presenting to mental health services for the first or second time with non-organic, non-affective psychosis. Interventions Assertive outreach with evidence based biopsychosocial interventions (specialised care group) and standard care (control group) delivered by community mental health teams.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
488
3
14

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 539 publications
(525 citation statements)
references
References 25 publications
20
488
3
14
Order By: Relevance
“…With signs that early interventions for severe mental illness [1,2] have at best only a modest impact on longer term outcome [3], a need for a long term care and support system that facilitates recovery and avoids institutionalization [4] is resurfacing [5,6]. Systematic research, however, has yet to promote the use of long-term care programs, such as the clubhouse model, despite their long-standing existence internationally.…”
Section: Introductionmentioning
confidence: 99%
“…With signs that early interventions for severe mental illness [1,2] have at best only a modest impact on longer term outcome [3], a need for a long term care and support system that facilitates recovery and avoids institutionalization [4] is resurfacing [5,6]. Systematic research, however, has yet to promote the use of long-term care programs, such as the clubhouse model, despite their long-standing existence internationally.…”
Section: Introductionmentioning
confidence: 99%
“…W 2010 r. Bird i wsp. opublikowali wyniki metaanalizy kilku dużych kontrolowanych badań na temat wczesnych interwencji w różnych ośrodkach na świecie -badania: COAST [93], LEO [94], OPUS [95], OTP [96], w której wykazali, że w okresie pierwszych pięciu lat trwania choroby takie wczesne i szerokie interwencje mają przewagę nad opieką standardową. Na podstawie wyników tej metaanalizy uważa się, że wczesna, kompleksowa interwencja u osób chorych na schizofrenię skutkuje istotną klinicznie redukcją ryzyka nawrotu choroby i ponownych hospitalizacji.…”
Section: Implikacje Terapeutyczneunclassified
“…The idea of early intervention programs for schizophrenic patients includes not only early detection of disorders, but also multidisciplinary, com-prehensive care for patients and their families in the form of specialized pharmacological and non-pharmacological therapy: family interventions, behavioral cognitive therapy, social skills training, and problem solving, help with getting a job and extensive psycho-educational interventions for patients and their families. In 2010, Bird et al published a meta-analysis of several large controlled studies of early intervention in different centers around the world -COAST [93], LEO [94], OPUS [95], OTP [96], in which they demonstrated that during the first five years of illness, such early and widespread interventions have the advantage over standard care. Based on the results of this meta-analysis, early intervention in schizophrenic patients is believed to result in a clinically significant reduction in the risk of relapse and re-hospitalization.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…However, there was little done to prove that the use of a multidisciplinary approach involving several professions, provided any clinical advantage to the patients. Later, with the development of Early Intervention in psychosis teams, it was possible to test the hypothesis that an Assertive Early Intervention multidisciplinary team provided better outcomes than treatment as usual in a standard multidisciplinary community mental health team (Agius 2007, Craig 2004, Nordentoft 2006). However this begs the fundamental question as to whether the use of a multidisciplinary approach actually gives any specific advantage to the patient.…”
Section: Introductionmentioning
confidence: 99%